Liprotide-encapsulated vitamin D3 modulates circulated PTH levels and improved bone microstructure - Shauma, Claradhita Ayu; Fulyani, Faizah; Pramono, Adriyan; Mahati, Endang; Putri, Sylvia Rahmi; Maulana, Reza Achmad; Anjani, Gemala (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2023)
Background: vitamin D (25(OH)D) is a fat-soluble vitamin that is unstable in the gastrointestinal environment and has low bioavailability. A protein-lipid complex (liprotide) can be used as a shell to increase vitamin D stability and bioavailability. Liprotide can also serve as a delivery system for transporting vitamin D to its intended site. Little attention has been paid to utilizing liprotide as a delivery system for vitamin D and evaluating its functional activity.Objective: to investigate the effect of liprotide-encapsulated vitamin D3 on PTH levels and bone microstructure in vitamin D and calcium (VD-Ca) deficient rats.Materials and Methods: an overall of 24 Wistar rats had been divided into four groups, a normal control group (K), a VD-Ca group without treatment (K-), a VD-Ca group with 180 IU/200 gBW/day free vitamin D3 (FVD3), and a VD-Ca group with 180 IU/200 gBW/day liprotide-encapsulated vitamin D3 (LVD3). Before and after 28 days of vitamin D intervention, blood samples were taken and analysed for serum PTH levels. The microstructure of the bone was analyzed using the Scanning Electron Microscope (SEM).Results: the VD-Ca rats supplemented with vitamin D3 (FVD3 and LVD3) had a significant decrease in serum PTH levels (p<0.001) and improved bone microstructure (p<0.05) compared to the (K-) group. The reduction of PTH in the LVD3 group was higher compared to the FVD3 group. The bone microstructure between the FVD3 and LVD3 groups is significantly different, as seen in the Ct.Wi parameter, with the LVD3 group having a higher Ct.Wi than the FVD3 group.Conclusion: liprotide-encapsulated vitamin D3 improves the serum PTH level and bone microstructure in a rat model of vitamin D and calcium deficiency.